Analisis Pelaksanaan Pelatihan dalam Meningkatkan Kualitas Pelayanan Departemen Tata Graha di Hotel Sanur Beach sanur - I Wayan Sunarsa (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study aims to analyze the implementation of training in improving the service quality of the department of housekeeping at Hotel Sindhu Beach Sanur. This research used descriptive analysis technique.  The data collection method was carried out by interviewing, documenting and distributing questionnaires. The results of the study indicate that the implementation of the training program has been going well, namely: (a) The assessment of needs and human resources for training is in accordance with the objectives set by the management of the Sindhu Beach Hotel Sanur, (b) The training objectives have been adjusted to the needs of the stewards of the description the work of the pramugraha that has been determined by management, (c) the preparation of training criteria has gone well, (d) the training techniques used have been adjusted to the material and the number of pramugraha participating in the training, (e) the training method used by the instructors has been effective in accordance with the delivery material to pramugraha, (f) Evaluation of training implementation focused on guest complaints and data on the implementation of tasks carried out by pramugraha.